BLOOD GLUCOSE RESPONSES TO CONVENTIONAL LEGUMINOUS DISHES IN NORMAL AND DIABETICS - S. Khan; M. L. Khan; N. Bhatty (Journal of Animal and Plant Sciences, 2009)
The glycaemic responses of conventional leguminous dishes including Mash (Vigna mungo), Moong (Vigna radiata), Masoor (Lens esculenta), Chana dhal (Cicer arietnum) and Biryani incorporated into the mixed meal and served with white boiled rice as conventionally consumed in Pakistan were studied in six normal and six diabetic subjects. Subjects were given a fifty gm carbohydrate portion of the different test meals in random order after an overnight fast. Taking the response of chapatti plus egg as 100 %, the relative glycaemic responses of the mixed meals containing Mash, Moong, Masoor, Chana dhal and Biryani were determined 91 ± 6.7, 111 ± 6.7,108 ± 6.8, 88 ± 6.2 and 101 ± 6.4 percent respectively in normal subjects and 102 ± 3.8, 123 ± 15.9, 107 ± 6.5, 87 ± 7.9 and 103 ± 3.6 percent in diabetic subjects. It was concluded that conventional leguminous dishes which containing white boiled rice as a mixed meal may be of less use in the dietary management of diabetes.
Keywords: Diet; Glycaemic response; Type II Diabetes mellitus and Conventional leguminous meals.